Investigation and Research on the Regularity of College Students’ Winter Vacation Life - Liujun Guan (Journal of Advanced Research in Education, 2024)
This study investigated and analyzed the winter vacation life patterns of college students, represented by 1577 college students. The survey found that college students have an insufficient attitude towards vacation learning, an irregular life, and are affected by family address, gender, major, and grade. This article will analyze it and put forward corresponding suggestions and countermeasures.